Guatemala's Late Pleistocene (Rancholabrean) fauna: revision and interpretation - Dávila, Lorena S.; Stinnesbeck, Sarah; Stinnesbeck, Wolfgang (Quaternary science reviews, 2019)
We present a revision, dating and interpretation of the Late Pleistocene megafauna of Guatemala based on paleontological material located in collections in the country and other fossils housed in the American Museum of Natural History, New York. Assemblages are dominated by proboscideans (Cuvieronius) and xenarthrans (Eremotherium, Glyptotherium), while co-occurring Equus and Mixotoxodon are significantly less frequent, and Holmesina, Palaeolama, Tapirus, Neocherus, Mammuthus and other ground sloth taxa (Paramylodon; Megalonyx) are rare. Contrary to published records the faunal assemblage is dominated by North American faunal elements. The underrepresentation of typical South American fauna therefore suggests a more southernly located biogeographic juncture between the two subcontinents, at least for the Late Pleistocene. The biogeographical barrier was either formed by the high mountain chains, or alternating periods of low and high precipitation that triggered the intermittent expansion of either grass- or woodland, thus leading to an alternating filter for either grazers or browsers. The presence of an oak-dominated forest vegetation with Mixotoxodon, Eremotherium and Cuvieronius supports high precipitation rates during MIS 3 and 2, followed by drought during the Late Pleistocene deglaciation. The expansion of grassland during the Younger Dryas period favored the migration of Mammuthus along the Mesoamerican Corridor, which is otherwise absent in Guatemala. Our data also suggest a survival of Cuvieronius into the early Holocene in the southeastern lowlands of Guatemala along the Motagua river. Our review is important as Guatemala is key to understanding migrations along the Mesoamerican Corridor that acted as a bridge but also as a filter of faunal interchange between North- and South America.